Financial Literacy and Fintech : A Double-Edged Sword for Millennial Investors’ Behavioral Biases - N., Sunil; B., Sathish Kumar (Indian Journal of Finance, 2025)
Purpose : The current research focused on investigating the moderating effect of financial literacy and financial technology on the heuristic behavior of millennials. Research Approach : The research was based on the primary data; a survey method questionnaire was prepared to collect the data needed for the present research. With the purposive sampling method, 526 responses were collected from millennial investors. The partial least square-structural equation modeling (PLS-SEM) method was applied to infer the moderating effect of financial literacy and financial technology on millennials’ heuristic behavior. Findings : The results showed that financial literacy significantly moderated the relationship between millennials’ heuristics and behavioral biases, whereas financial technology had no moderating effect. Research Implications : Millennial investors were slammed or benefited by the stock market performance. The research aimed to help them understand their behavioral changes during market anomalies. Financial advisors and regulatory bodies should consider the study’s outcome as it contributes to mitigating the misconception of behavioral bias. Originality : There are numerous articles describing individual investors’ behavioral biases, but the current research’s uniqueness was to measure the moderating effect of financial literacy and financial technology on millennials’ heuristics and behavioral biases and a significant contribution to the world of research in behavioral finance.